Peningkatan Hasil Belajar Matematika menggunakan Model Contextual Teaching and Learning di Kelas IV SDN 235/VI Tanjung Mudo II - Aspihan, Hamid; Hidayat, Puput Wahyu (Master of Pedagogy and Elementary School Learning, 2025)
The purpose of this study is to improve mathematics learning outcomes in fraction addition operations for Fourth Grade students at SDN 235/VI Tanjung Mudo II and to explore how the Contextual Teaching and Learning (CTL) approach can enhance learning in this area. This classroom action research was conducted with Fourth Grade students during the second semester of the 2024/2025 academic year at SDN 235/VI Tanjung Mudo II. This research was carried out in two cycles aimed at improving students' performance in fraction addition operations. The findings indicate that the use of the CTL approach significantly improved students' mathematics learning outcomes, both in quality and quantity. This approach aligns with the desired learning outcomes, fosters an independent learning atmosphere, and encourages creativity and active participation by connecting learning concepts to real-life contexts.